2021
DOI: 10.3389/fneur.2021.722334
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regional Pain Syndrome: Thalamic GMV Atrophy and Associations of Lower GMV With Clinical and Sensorimotor Performance Data

Abstract: Results on gray matter alterations in complex regional pain syndrome (CRPS) showed heterogeneous findings. Since CRPS is a rare disease, most studies included only small and heterogeneous samples resulting in a low reliability of findings between studies. We investigated 24 CRPS patients with right upper limb affection in the chronic stage of disease using structural MRI and clinical testing. We focused on gray matter volume (GMV) alterations of the brain in comparison to 33 age matched healthy controls, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…A total of 411 studies were found from three databases; 129 results were removed because of duplication, 270 of the remaining 282 studies were removed after screening the title and abstract, and 7 of the remaining 12 studies were removed after browsing the full text, meaning 5 studies were included in this meta-analysis [ 1 , 11 , 12 , 13 , 14 ]. A detailed search flow diagram is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 411 studies were found from three databases; 129 results were removed because of duplication, 270 of the remaining 282 studies were removed after screening the title and abstract, and 7 of the remaining 12 studies were removed after browsing the full text, meaning 5 studies were included in this meta-analysis [ 1 , 11 , 12 , 13 , 14 ]. A detailed search flow diagram is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it was reported that GMV in the dorsomedial prefrontal cortex of patients with CRPS was higher than that of HCs [ 1 ], whereas Barad et al found that patients with CRPS had higher GMV in the right hypothalamus, left dorsal putamen, and left inferior temporal lobe, as well as lower GMV in the left orbitofrontal cortex, left middle cingulate cortex, right middle cingulate cortex, left posterior middle cingulate cortex, left dorsal insula, and left anterior middle cingulate cortex at the same time [ 13 ]. Due to the limited research samples, heterogeneous and unreliable findings may exist in CRPS studies [ 14 ]. Therefore, it is of great necessity to perform a systematic review and meta-analysis exploring the reliable GMV alterations in CRPS.…”
Section: Introductionmentioning
confidence: 99%
“…MI training appears to activate areas of the brain involved in movement preparation 15,20,61,67 . It is plausible that MI helps CRPS patients by activating other gray matter pathways 12,68,69 , by improving body schema deficits 14,[70][71][72][73] , or because CRPS or chronic pain patients may not be so different from healthy patients in their MI abilities. MI training appears to be an effective treatment, but not to correct MI deficit 26 .…”
Section: Discussionmentioning
confidence: 99%
“…MI training appears to activate brain areas involved in movement preparation 15,19,52,57 . It is plausible that MI helps patients with CRPS by activating other gray matter pathways 12,58,59 , or improving body schema deficits 14,[60][61][62][63] . MI training appears to be an effective treatment, but not to improve a MI deficit 25 .…”
Section: Discussionmentioning
confidence: 99%
“… 2 Both exhibit loss of inhibitory input to the cortex, increased cortical excitability, 1 , 3 and thalamic degeneration. 1 , 4 CRPS and CBS share the same pain generating mechanism as central post‐stroke pain. In each condition, there is sensory deafferentation and reduction in thalamic and sensory input to the cortex, which produces pain.…”
mentioning
confidence: 99%